AN ANALYSIS OF SEMIOTIC IN THE FILM RAYA AND THE LAST DRAGON BY CARLOS LOPEZ ESTRADA - Adam, Maryam; Maunty, Sarifin A; Hasanah, Atiq Aqiqotul (LPPM STISIPOL Mujahiddin, 2024)
The purpose of this research is to find out what types of signs are found in the film Raya and the last dragon. The research method used is descriptive qualitative, namely the researcher will make direct observations of the contents of the signs Selements of signs and meanings in the film Raya and the Last Dragon based on Roland Barthes' theory, namely to analyze the meaning of markers, signs and the order of denotative, connotative meanings, so that researchers find hidden meanings in the film.This film attempts to convey the social reality of social division and conflict caused by prejudice, hatred, greed and the desire for power